2009
DOI: 10.1007/s11284-009-0645-y
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient relocation, hydrological functions, and soil chemistry in plantations as compared to natural forests in central Yunnan, China

Abstract: Nutrient relocation, hydrological functions, and soil chemistry in plantations as compared to natural forests in central Yunnan, China Abstract The relocation of nutrients among dominant plant species, along with hydrological functions and soil chemistry in five plant communities, including Eucalyptus plantation, Pinus plantation, shrubland, semi-natural, and natural secondary forests were investigated in central Yunnan, China. The nutrient P, N, and K accumulation in above-ground biomass of Eucalyptus smithii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 39 publications
1
16
1
Order By: Relevance
“…Our results showed that soil N in the GPES region was not high (total N: 0.78 9 10 3 mg/kg; available N: 87.4 mg/ kg), similar to results obtained by Hou et al (2010) from non-GPES in Central Yunnan. It is hard to identify nutrient limitation from the mean soil N contents (Han et al 2011); the mean L N:P found in GPES was just 4.96; therefore, according to the eco-stoichiometry theory, N was limited at our study site (Güsewell 2004).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our results showed that soil N in the GPES region was not high (total N: 0.78 9 10 3 mg/kg; available N: 87.4 mg/ kg), similar to results obtained by Hou et al (2010) from non-GPES in Central Yunnan. It is hard to identify nutrient limitation from the mean soil N contents (Han et al 2011); the mean L N:P found in GPES was just 4.96; therefore, according to the eco-stoichiometry theory, N was limited at our study site (Güsewell 2004).…”
Section: Discussionsupporting
confidence: 88%
“…Our results showed that soil in the GPES region had extremely high total P (6.57 9 10 3 mg/kg) and available P content (381.54 mg/ kg), which were significantly higher than the results obtained by Hou et al (2010) from non-GPES regions in Central Yunnan. The soil P level in GPES in Central Yunnan was significantly higher than the P-enriched threshold identified by Delorme et al (2000), where GPES had higher soil P content and variability, and was very different from other P-enriched regions identified in earlier studies, e.g., pasture and farmland (Delorme et al 2000;Read 2012;Sharma and Sahi 2005).…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Song ( 2013 ) asserted that the subtropical evergreen broad-leaved forest of China corresponds to the region from 23° to 33° N and from 98° to 123° E. In fact, within Yunnan the forest extends west to c. 97°32′ E (e.g. SW China, especially Yunnan, is home to the most diversifi ed subtropical EBLFs to be found in East Asia (Tang and Ohsawa 2009 ;Tang 2010 ;Tang et al 2013 ). Chayu and Motuo in Yaluzangbujiang, though in deep gorges at 100-600 m asl, very limited patches of the tropical rain forest dominated by Dipterocarpus are found).…”
Section: Forest Typesmentioning
confidence: 99%
“…The most important factors in the loss of plant diversity are habitat fragmentation and degradation in the subtropical areas of SW China (Tang 2010 ). In Yunnan Province, 90 plant species were recorded in the national priority protection list/ inventory (Li et al 2003 ).…”
Section: Threats Of Habitat Fragmentation and Degradationmentioning
confidence: 99%